Analisis Pengaruh Kualitas Produk, Citra Merek dan Harga terhadap Kesetiaan Pelanggan pada Merek Erigo di Medan - Hendy, Hendy; Robin, Robin; Aranggoh, Huliyan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to analyze the impact of product quality, brand image, and price on customer loyalty towards the Erigo brand in Medan. The research methodology used is a descriptive quantitative method. The type of data used is quantitative data, which is obtained in numerical form. Data sources include primary data and secondary data. Primary data is obtained from questionnaires distributed to respondents, while secondary data is gathered from previous data or literature studies. The population in this study comprises all Erigo consumers in Medan. The sampling technique employed is the Lemeshow formula for unknown population with a 10% tolerance, resulting in 97 respondents. Data testing is carried out through validity tests, reliability tests, classical assumptions, and hypothesis testing. The results indicate that product quality does not have a partial effect on customer loyalty. Brand image has a positive and significant partial effect on customer loyalty. Price has a positive and significant partial effect on customer loyalty. Product quality, brand image, and price have a positive simultaneous effect on customer loyalty with a coefficient of determination of 34.5%.